(untitled) (Journal of Medical Sciences, 2018)
Radiation is widely used in the diagnosis and treatment of many diseases, but limited usage of radiation for medical purposes is important. When the human body is exposed to radiation doses over 1 Sievert, gastrointestinal, neurological and hematological disorders in the acute stage appear. Exposure to low doses of radiation over a long period of time may result in genetic effects such as cataract, cancer, shortage in lifespan, or transmitting of genetic disorders to future generations. Employees in these practices should be protected from radiation effectively and be provided with safety devices. The level of awareness concerning radiation protection influences the staff behavior. If they do not have, enough information related to radiation safety, their action will not be safe and will result in adverse effects. This questionnaire was designed and introduced to medical staff in Brack Hospital at Al-shatti region to evaluate their knowledge levels about ionizing radiation and their awareness about radiation safety. The statistical comparison between the groups was analyzed using the Statistical Package for the Social Sciences (SPSS) program. The results showed that they lack of knowledge and practices toward radiation safety related to radiological imaging and training programs are recommended.